A case of prenatal diagnosis of diastrophic dysplasia in the 1st trimester of pregnancy - S. A. Tyo (Медицинский вестник Юга России, 2022)
A case of early prenatal diagnosis of diastrophic dysplasia at 13 weeks 2 days of gestation is described. During ultrasound screening of the first trimester, fetal changes characteristic of this form of systemic skeletal dysplasia were revealed – micrognathia, micromelia, flexion contracture in the elbow and knee joints, pathognomonic abduction of the thumb of the hands and feet for diastrophic dysplasia (hitchhiker thumb), varus deviation and postaxial polydactyly of the feet, in combination with by a significant increase in the nuchal translucency. Pregnancy was interrupted for medical reasons. The possibilities of ultrasound diagnostics of diastrophic dysplasia by two- and three-dimensional ultrasound using are shown.